Can the Subaltern Speak? The Politics of Identity and Difference in Italian Postcolonial Women's Writing. - Wright, Simona (Italian Culture (Michigan State University Press), 2004)
Discusses the politics of identity and difference in Italian postcolonial women's writing. Interest of Italians to the works; Impact of narratives of African immigrants writing in Italian; Desire for emergence, empowerment, and self-expression that saturated the thematic fabric of immigrant texts; Process of linguistic reappropriation and redenotation.